Paranode length in the prefrontal cortex of subjects with major depression and rats under chronic unpredictable stress - Miguel-Hidalgo, José Javier; Kelly, Isabella; Rajkowska, Grazyna (Journal of affective disorders, 2025)
Experimental studies of major depressive disorder (MDD) and stress reveal connectivity disturbances of the prefrontal cortex (PFC) that may involve molecular and morphological changes in myelin and the axons it enwraps. These alterations may also affect the nodes of Ranvier (NR), myelin-bare axon stretches along myelin sheaths necessary for action potential propagation, as well as the paranodes, specialized regions of the myelin sheath flanking NRs. Thus, we investigated whether paranode length and the labeling of paranode marker CASPR in PFC white matter (WM) differed in MDD subjects and chronic stress-exposed rats, as compared to their respective controls. Histological sections were obtained from postmortem PFC blocks of 11 subjects with MDD diagnosis and 11 non-psychiatric controls as well as from 6 rats subjected to chronic unpredictable stress (CUS) and 6 non-stressed controls. NRs and paranodes were detected by immunofluorescence with specific antibodies to paranodal protein CASPR. Differences in paranode length and CASPR immunoreactivity were assessed by analysis of covariance and t-tests. In MDD, both paranode length and overall CASPR immunoreactivity were significantly lower than in non-psychiatric controls, while paranode length and CASPR labeling were positively correlated with age. However, those variables did not statistically differ between CUS-exposed and non-exposed rats. Shorter paranodes and lower CASPR immunoreactivity in MDD subjects suggest alterations in paranodal myelin, which may contribute to depression-related connectivity changes. However, without comparable changes in CUS-exposed rats, mechanisms other than the stress response cannot be ruled out as contributors to paranode alterations in MDD. •Measured prefrontal paranode length and CASPR in depressed humans and stressed rats.•Paranode length and CASPR immunoreactivity were lower in subjects with depression.•Human subjects showed positive correlation of age with paranode length and CASPR.•Short paranodes and low CASPR may contribute to connectivity changes in depression.